2017
DOI: 10.1002/jsfa.8414
|View full text |Cite
|
Sign up to set email alerts
|

Cardamom supplementation improves inflammatory and oxidative stress biomarkers in hyperlipidemic, overweight, and obese pre‐diabetic women: a randomized double‐blind clinical trial

Abstract: Cardamom could improve some parameters of inflammation and oxidative stress in pre-diabetic subjects. Thus it may be useful in reducing complications associated with inflammation and oxidative stress in these patients. Copyright © 2017 Society of Chemical Industry © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 32 publications
(72 reference statements)
2
25
1
1
Order By: Relevance
“…A significant decrease in concentration of C‐reactive protein was seen by I. gabonensis (Ngondi et al, ), pomegranate (Hosseini et al, ), Palmaria palmata (Allsopp et al, ), puerh tea (Chu et al, ; Yang et al, ), Opuntia ficus‐indica (Godard et al, ), cardamom (Kazemi et al, ), Salba‐chia ( S. hispanica L.; Vuksan et al, ), and the combination red orange, grapefruit, sweet orange, and guarana (Dallas et al, ; Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant decrease in concentration of C‐reactive protein was seen by I. gabonensis (Ngondi et al, ), pomegranate (Hosseini et al, ), Palmaria palmata (Allsopp et al, ), puerh tea (Chu et al, ; Yang et al, ), Opuntia ficus‐indica (Godard et al, ), cardamom (Kazemi et al, ), Salba‐chia ( S. hispanica L.; Vuksan et al, ), and the combination red orange, grapefruit, sweet orange, and guarana (Dallas et al, ; Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…, pomegranate(Hosseini et al, 2016), Palmaria palmata(Allsopp et al, 2016), puerh tea(Chu et al, 2011;Yang et al, 2014), Opuntia ficus-indica(Godard et al, 2010), cardamom(Kazemi et al, 2017), Salba-chia (S. hispanica L.;Vuksan et al, 2017), and the combination red orange, grapefruit, sweet orange, and guarana(Dallas et al, 2014; Figure 2).…”
mentioning
confidence: 99%
“…Han and Parker (2017) reported that cardamom essential oil has potential anti-inflammatory and immunomodulatory properties. Recently, Kazemi et al (2017) claimed that cardamom improved inflammatory indices and oxidative stress in pre-diabetic women. However, eugenol and acetyleugenol are the major compounds of clove which displayed potential immunomodulatory/anti-inflammatory effects.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…This spice is a good source of polyphenolic compounds such as quercetin, kaempferol, luteolin, pelargonidin, gallic acid, caffeic acid, and limonene, which have antioxidant properties (Deepa, Ayesha, Nishtha, & Thankamani, 2013;Nair & Kutty, 2004;Sharma, Sharma, & Kaur, 2011). Therapeutic effects of cardamom have been found in diabetes (Azimi, Ghiasvand, Feizi, Hariri, & Abbasi, 2014;El-Yamani, 2011), cancer (Kaefer & Milner, 2008), inflammation (Kazemi et al, 2017), gastrointestinal disorders (Jamal, Javed, Aslam, & Jafri, 2006), and hypertension (Verma, Jain, & Katewa, 2009). Recently, evidence from a number of clinical studies (Aghasi et al, 2019;Azimi et al, 2014;Daneshi-Maskooni et al, 2019;Fatemeh et al, 2017;Verma, Jain, & Singh, 2012) focused on the beneficial effects of cardamom on circulating lipids and lipoproteins; however, the existing trials yielded inconsistent results.…”
Section: Introductionmentioning
confidence: 99%